2022
DOI: 10.1101/2022.09.12.507594
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mining for ions: diagnostic feature detection in MS/MS spectra of post-translationally modified peptides

Abstract: Post-translational modifications (PTMs) are an area of great interest in proteomics, with a surge in methods to detect them in recent years. However, PTMs can introduce complexity into proteomics searches by fragmenting in unexpected ways. Detecting post-translational modifications in mass spectrometry-based proteomics traditionally relies on identifying ions shifted by the masses of the modifications. This presents challenges for many PTMs. Labile PTMs lose part of their modification mass during fragmentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…Fully enzymatic MSFragger search was performed using strict-trypsin settings (i.e., allowing cleavage before Pro) and allowing 2 missed cleavages, precursor and fragment tolerances of 20 and 10 ppm respectively, mass calibration, fixed Cys carbamidomethylation, and variable modifications of Met oxidation and Protein N-terminal acetylation. 4SU crosslinking was searched as both the intact nucleoside (+226.0594 Da) and the base only (+94.0168 Da), as frequent in-source fragmentation of nucleoside was noted by Bae et al and which we confirmed using the PTM-Shepherd diagnostic mining module (23). For labile search, +94 and +226 were searched as mass offsets on any amino acid, with labile mode active, no diagnostic or peptide remainder ions, and a fragment remainder ion of +94.…”
Section: Rna-xl Searchsupporting
confidence: 67%
See 3 more Smart Citations
“…Fully enzymatic MSFragger search was performed using strict-trypsin settings (i.e., allowing cleavage before Pro) and allowing 2 missed cleavages, precursor and fragment tolerances of 20 and 10 ppm respectively, mass calibration, fixed Cys carbamidomethylation, and variable modifications of Met oxidation and Protein N-terminal acetylation. 4SU crosslinking was searched as both the intact nucleoside (+226.0594 Da) and the base only (+94.0168 Da), as frequent in-source fragmentation of nucleoside was noted by Bae et al and which we confirmed using the PTM-Shepherd diagnostic mining module (23). For labile search, +94 and +226 were searched as mass offsets on any amino acid, with labile mode active, no diagnostic or peptide remainder ions, and a fragment remainder ion of +94.…”
Section: Rna-xl Searchsupporting
confidence: 67%
“…With user-specified options for diagnostic ions, peptide remainder masses, and fragment remainder masses, a wide variety of labile modifications can be easily searched with MSFragger. The labile mode search can leverage the fragment ions discovered by our recently described fragment ion discovery module in PTM-Shepherd (23), allowing labile mode to be used without requiring manual annotation of fragmentation pathways for new modifications. Localization of labile modifications has long been a significant obstacle to PTM analyses, and remains so in cases where PTMs dissociate without forming any fragment remainder masses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FragPipe with MSFragger labile search 72 and PTM-Shepherd diagnostic feature detection 73 revealed a high intensity and highly specific dihydrooxazolium ion unique to a subset of sCLIP reagents. By harnessing this dihydrooxazolium ion, we developed the sCLIP isobaric platform, which is a low cost six-plex isobaric labeling strategy in which the mass balancer and reporter are incorporated into cysteine-reactive iodoacetamide alkyne probe and sCLIP capture reagent, respectively (Figure 1C).…”
Section: Significant Inroads Have Already Been Made Into Realizing Th...mentioning
confidence: 99%